أثر تنمية القطاع البنكي على النمو الإقتصادي دراسة قياسية حالة الجزائر 1990-2020 - عمران أسماء سوزان; محمدي خيرة; عامر إبراهيم (جامعة عمار ثليجي الاغواط, 2022)
This study aims to test the impact of the development of the banking sector on Algeria's economic growth over 1990 - 2020 (using the annual data of three separate variables of (Private sector loans to GDP, interest rate on loans to GDP, government spending to GDP), economic growth as a dependent variable, this study applies an Autoregressive Distributed Lag model (ARDL), and an Error Correction Model in order to asses a long-run equilibrium relationship between variables. The findings show that there is a long-term equilibrium between variables, and demonstrate a positive impact of interest rate on economic growth rates. However, government spending and loans to private sector had a negative impact on economic growth in short and long terms, which may be explained by the inefficient and lack of independence of Algerian banking sector.